Reputation and eWOM in accommodation decision-making: insights from Generation Z users. - Pérez-Aranda, Javier Ramón; Tolkach, Denis; Panchal, Jenny H. (Emerald, 2024)
Purpose This study aims to explore the relationship between Generation Z (or Gen Z) consumers’ decision-making styles and electronic word-of-mouth (eWOM) use in the tourism sector. Drawing on the consumer style inventory (CSI) model and the theory of reasoned action (TRA), the research examines how specific decision-making styles influence Gen Z’s propensity to use eWOM recommendations for accommodation choices. Design/methodology/approach The study uses structural equation modelling to analyse data collected from 296 Gen Z users of Booking.com. The CSI model is adapted to the analysed context and attributes – impulsive, recreational, sustainable, fashion-conscious and perfectionist attitudes – are examined to determine their impact on eWOM use intention and actual eWOM use. Findings Three of the hypothesised relationships in the model were validated. Specifically, the results suggest that the attitudes of sustainable and perfectionist consumers influence the intention to use eWOM. Furthermore, use intention is positively associated with the actual use of eWOM. Practical implications For marketers and tourism businesses, understanding the decision-making styles of Gen Z can inform the development of targeted marketing strategies that emphasise quality and sustainability. Highlighting these aspects in online reviews and eWOM platforms can enhance engagement with Gen Z consumers. Originality/value This research advances the understanding of eWOM behaviour by integrating CSI and TRA theories in the context of Gen Z’s tourism decision-making. It provides empirical evidence on the significant role of perfectionist and sustainable attitudes in shaping eWOM intentions, contributing to the literature on consumer behaviour and digital marketing in tourism.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/36866
Keywords: Turismo - Efectos de las innovaciones tecnológicas; Consumidores - Conducta; Viajeros - Toma de decisiones; eWOM; Consumer style inventory; Generation Z; Consumer decision-making